Early Adverse Effects of Foam Sclerotherapy for Varicose Veins: An Experience of 50 Sclerotherapy Sessions - Anis Ahmed, Yasmeen Iqbal, Sidra Akbar, Syed Aamer Hussain, Tariq Jamil (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Foam injection sclerotherapy for treating varicose veins is a newly emerging and minimally invasive technique. Its safety profile needs to be investigated. Objective: We documented the adverse effects associated with foam injection sclerotherapy occurring in the first 24 hours and then at 2 and 4 weeks of follow up visits. Material and Methods: This cross-sectional study was conducted at Department of Surgery in Benazir Bhutto Hospital, affiliated with Rawalpindi Medical University, Rawalpindi from 1st July 2021 till 30th June 2022; on 50 patients of varicose veins. A duplex ultrasound was done in all patients. Varicose veins were classified using the CEAP system. Patients having C1 and/or C2 varicose disease with isolated GSV incompetence on duplex ultrasound were included. Results: Only minor complications were encountered and no serious complication was seen. The minor side effects included nausea, hyperpigmentation, matting, headache, vomiting, pruritus around injection site, vomiting and shortness of breath. Serious complications like anaphylactic shock, stroke, TIA, deep venous thrombosis, superficial venous thrombosis, tissue necrosis and skin necrosis were not encountered in any patient. Conclusion: Injection sclerotherapy with sodium tetra decyl sulphate in the foam form for the treatment of varicose veins is a safe modality; since only minor complications were encountered and no serious complication was seen. Keywords: Varicose veins; Foam sclerotherapy; Duplex ultrasound; Complications; Side effects